ANATOMI BATANG KELAPA (COCOS NUCIFERA L.) - Nenny S Sudarna (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The anatomical features of coconut stem at several depth and heights were each observed. The nature stem has 22 to 30.5 cm in diameter and the hard pheripheral region of the stem is 4-8 cm in thickness.The cross section of coconut stem consists of four region. The outer region of the stem with the thichness of about 0.5 cm is epidermis and the inner region is the pheripheral region which can be divided into eksopheripheral and endoperipheral regions. Eksopheripheral region is 0.5-1 cm consists mainly of fiber tissues; the endopehripheral region consists mainly of vibrovascular bundles, about 4-8 cm in thickness. The innest region is central portion, which consists mainly of parenchyma tissues.There is a relation between frequency and diameter of vibrovascular bundles in stem, where the higher the frequency of vibrovascular bundles (229 bundles/sq.cm), the smalller the diameter of vascular bundles (103 bundles micron).The fiber dimension varies either along or across the stem as follows: length 1191.6 to 1980.8 microns, diameter 28.3 to 42.6 microns, wall thickness 5.2 to 13.8 microns. The runkell ration varies from 0.5 to 1.9.